ANALISIS GENEALOGI DAN TRANSMISI SANAD AL-QUR’AN PADA KOMUNITAS MUSLIM INTERNASIONAL MALAYSIA - Sofiah Sofiah; Ziyadulhaq Ziyadulhaq; Ade Naelul Huda (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
This research examines the history and bibliography of the Qur'anic chain of transmission (sanad) of Riwayat Hafs and the process of granting the Qur'anic certificate (ijazah) to participants in the Qur'anic Sanad certificate program at the Itqan Education Foundation, a private institution officially established in Kuala Lumpur, Malaysia, in 2009. This field research is a descriptive study using qualitative methods with a historical approach. It examines historical sources related to the Qur'anic chain of transmission (sanad) of Riwayat Hafs, which is popular among Muslims in Malaysia. Data collection was conducted through interviews, observation, and documentation. The results of this study conclude that the genealogy of the Qur'anic chain of transmission (sanad) studied by the author is considered to be of high quality, requiring strict qualifications and a verification process to obtain this certificate. Until in the end, only participants who memorize the entire Al-Qur'an and fulfill all the qualifications can receive a diploma from the Al-Qur'an.